Social networks and entrepreneurships – does personal networks matters? - Choban, Ugur; Noor Azuan Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Institutional and social network are several major research traditions in the business and management areas. This paper examines the role of owner/managers’ social network on entrepreneurship initiatives and the underlying socio-cultural factors promoting or impeding SME development in Kazakhstan. A semi-structured interviews were carried-out with thirteen SME owners/managers in Almaty Kazakhstan. It is found that personal networks in general social networks have significant implications on a variety of entrepreneurial activities. SMEs still need to utilize their personal social networks to substitute for formal institutions. Normative institutional elements such as legal and moral are still major factors driving entrepreneurial activities but still lagging behind regulative and cognitive institutional transformation. Business ties and networking ability may mitigate the necessity for external financing. One of the major implication in this study is the need for SME owners/managers to build personal networks and to keep and maintain this network with their peers as well as the government not only for extra information but even for the sustainability of their business. To do this, SME owners/managers need to be regularly in contact with their peers and government officials, offering helps when needed, collaborate on projects, share their goals, get connected on social media and also joining networking events.